Common enemies : disease campaigns in America - Best, Rachel Kahn, 1982- (Oxford University Press, 2019)
Drawing on a century of data, Common Enemies reveals why disease campaigns are the battles Americans come together to fight, why certain diseases rose to prominence, and how fighting one disease at a time changes the way we distribute resources, conceptualize problems, and promote health. Combining quantitative and qualitative analyses, Rachel Kahn Best persuasively demonstrates how disease campaigns have created unintended consequences for health policy.